THE DYNAMICS OF TEACHERS MOTIVATION PATTERNS AND THEIR IMPACT ON STUDENTS LEARNING ACTIVITIES AT AR ROUDLOH ISLAMIC ELEMENTARY SCHOOL - Achmad Faisol; Muhammad Nashir; Abu Aman Siddiq Al Ghafir; Nur Ali; Djoko Supriatno (PGMI Fakultas Tarbiyah Universitas Islam Jember, 2025)
This study analyzes the relationship between teacher motivation and student learning behavior at MI Ar-Roudloh, Indonesia. The decline in student participation in learning is suspected to be related to variations in teacher motivation. Using a quantitative method with an ex post facto correlational design, the study involved 20 teachers and 40 students as samples. Data were collected through questionnaires and documentation of student learning outcomes, then analyzed using simple linear regression. The results showed a positive and significant effect of teacher motivation on student learning activities (r = 0.712, p < 0.05). These findings support Self-Determination Theory (SDT), which emphasizes the role of intrinsic teacher motivation in creating a learning environment that fosters student engagement. Practically, these results can serve as a basis for madrasahs to enhance teacher motivation to improve the quality of learning.